Niagara Falls, or does it? - Winkler, Henry, 1945- (Winkler, Henry, 1945- Hank Zipzer, 2003)
Fourth-graders Hank, Ashley, and Frankie are excitedly preparing for a magic show at the Rock 'N Bowl when Hank's creative alternative to an English essay lands him in detention and grounded the week of the show.